D6.1 ATHENA website - Hadjimitsis, Diofantos G.; Agapiou, Athos; Lysandrou, Vasiliki; Schreier, Gunter; Lasaponara, Rosa (My University, 2016)
The ATHENA website (www.athena2020.eu) is considered one of the most important dissemination tool of the project. The website is designed aiming to be simple, functional and intuitive for the project stakeholders’ and different types of audience. The content of the website includes information such as a brief description of the ATHENA project including the objectives, information about the consortium, all the research relevant material, documents such as publications, newsletters, etc. News and events are also provided by the website. The website will be systematically updated so as to indicate the progress of the project. ATHENA’s website includes also a Members area (i.e. Intranet) so as to be used as a management tool by the partners.
Keywords: ATHENA project; Website